FACTORS AFFECTING MOTIVATION OF PUBLIC PRIMARY SCHOOL TEACHERS. A SURVEY OF PUBLIC PRIMARY SCHOOLS IN THIKA MUNICIPALITY - Ng'ang'a, Rosalid Njoki; Muturi, Dr. Willy (African Journal of Education and Practice, 2016)
Purpose: The purpose of this study was to investigate the factors affecting motivation of public primary school teachers. A survey of public primary schools in Thika municipality. Methodology: This study adopted a descriptive survey design. The target population of this study was all the teachers "˜of public primary schools in Thika Municipality. According to the Education Office of Thika Municipality, there are 23 public primary schools in Thika Municipality. A sample of three teachers per school was taken. This implied that a total sample size of 66 teachers. A stratified random sampling was adopted to identify the three teachers from a school. The criteria for choosing the teachers was based on three strata, that is, a head teacher, a teacher from upper primary and a teacher from lower primary. Primary information was gathered by use of a questionnaire and SPSS version 20 was used as an analysis tool. Results: The finding implies that the working environment was poor and not conducive for the teachers. The results also indicated that the Correlation between motivation and working environment is positive significant (r=0.695, p value < 0.000). The findings imply that motivation has significant effect on working environment. Hence, poor working environment leads to low motivation and good working environment leads to high motivation. The finding implies that there the remuneration is low hence low motivation and poor performance. Findings reveal that the correlation between motivation and remuneration is positive significant (r=0.488, p value < 0.000). The findings imply that motivation has significant effect on remuneration. Hence, poor remuneration leads to low motivation and good remuneration leads to high motivation Results indicate that poor work load management leads to low motivation. Findings show that correlation between motivation and workload is positive significant (r=0.478, p value < 0.000). The findings imply that motivation has significant effect on workload. Hence, poor work load management leads to low motivation and good work load management leads to high motivation. Results indicate that poor teaching facilities lead to low motivation. Findings show that correlation between motivation and teaching facilities is positive significant (r=0.282, p value < 0.029). The findings imply that motivation has significant effect on teaching facilities. Hence, poor teaching facilities lead to low motivation and adequate teaching facilities leads to high motivation. The study concluded that poor working environment leads to low motivation and good working environment leads to high motivation. It was concluded that poor remuneration leads to low motivation and good remuneration leads to high motivation. Results also led to conclusion that poor work load management leads to low motivation and good work load management leads to high motivation. Furthermore, poor teaching facilities lead to low motivation and adequate teaching facilities leads to high motivation. Unique contribution to theory, practice and policy: The study recommends that working environment in public school teachers so should greatly improve. This is because of non-conducive environment acts as an impediment to motivation. This calls for policy intervention from the government departments concerned with education and vision 2030. Extensive need for new renovated of school's facilities e.g., offices should be effectively addressed so as to enhance teacher's motivation and birth of an educated society.